Inovasi Produk Pembiayaan Mikro dalam Pengembangan Usaha Kecil Menengah Berbasis Syariah - Kharisma Tri Buana Dewi; Fauzatul Laily Nisa (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
Small and Medium Enterprises (SMEs) play an important role in the Indonesian economy. However, access to financing is still a major obstacle to the growth of SMEs. Islamic financial institutions have great potential to support SME financing through innovative products that comply with sharia principles. This study aims to analyze the innovation of Islamic microfinance products in the development of SMEs. The research method used is a qualitative approach with literature studies and in-depth interviews. The results show that product innovations such as mudharabah, musyarakah, murabahah, and qardh financing play a significant role in meeting the financing needs of SMEs. The research also identified challenges and opportunities for the development of Islamic microfinance products for SMEs in the future.